Inside Victims, Outside Offenders: A Case Study on Crime Reporting - Füstös, Mónika (Magyar Rendészet, 2023)
In political and media rhetoric throughout Europe, migrants and refugees are often linked to crime; especially to gender-based crimes. This paper, focusing on Hungary, examines whether media discourses perpetuate this image and to what extent do other attributes of offenders (such as ethnicity and class) influence the way the media represent those involved in rape cases. The 720 articles sampled for this study were analysed using qualitative content analysis and critical discourse analysis, with Lindgren and Lundström’s model on inside victims/offenders and outside victims/offenders and Nils Christie’s theory on ideal victims being applied to the findings. Results show that the media in Hungary is more likely to grant victim status to those who are insiders (Hungarian, white, middle class) when their offenders are outsiders (migrant, Roma, lower class), while socially marginalised offenders are automatically externalised. The paper also shows that marginalised people are externalised collectively, while insiders are externalised individually. The application of Christie’s theory further strengthens the relational hypothesis that the ideal (or outsider) offender makes the ideal victim.